The role of industrial policy in market-friendly economies - case of Covid-19 vaccine R&D and its manufacturing in India and its contrast with the US$1 (BIIs - Mani, Sunil (Economic and Political Weekly)
The paper surveys the status of vaccine research and development and its manufacture in India and discusses the fact that the country has used industrial policy instruments rather sparingly in jump-starting R&D and manufacturing of vaccines for COVID-19 vaccines. This is despite India$1 (Bs acknowledged innovation capability. The paper also contrasts the Indian case with that of the United States case discussed in Part 1 of this two-part paper.- Reproduced s